Recent observations on religion education in South Africa - Nogueira-Godsey, Elaine (British journal of religious education, 2016)
The article presents recent observations on religious education in South Africa. It says that in 2003, the Minister of Education, Kader Asmal, enforced the National Policy on Religion in 2003. It adds that the policy offered a new framework to market diversity by educating young people about religions of others as well as respect towards freedom of religious expression.